(3YQGFS GdHjGf aj MbGFb GdbQBfs - (3CHh eMeO QhRHgGf Hf CHj fUQ GdHbdj GdTjQGRj, GdHbdj,J (B606 (3g` s ((3eMeO Hf MSf Hf eMehO GdeSHMi s)
(3ChdgG (B:s
(3GdMeO ddg cGf ai CRd RehLhO HhLhOg hPGJg UaGJg eYGOf LhOg s
(3BNQgG (B:s
(3hGdMeO ddg MeO GdGfbWGY dg hGdfJgGA hGdUdGI hGdSdGe Ydi SjO GdQSd eG OGeJ GdCQV hGdSeGA hGdMeO ddg hMOg s
(3Gdajde bSe Edi Qbejfs
(3HbjJg Qbe (B153 (3chjJs
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ hGdBjGJ GdcQjeI HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJaSjQ hYdhe GdbQBfs